2017
DOI: 10.1371/journal.pone.0180092
|View full text |Cite
|
Sign up to set email alerts
|

Receptor for advanced glycation endproducts (RAGE) maintains pulmonary structure and regulates the response to cigarette smoke

Abstract: The receptor for advanced glycation endproducts (RAGE) is highly expressed in the lung but its physiological functions in this organ is still not completely understood. To determine the contribution of RAGE to physiological functions of the lung, we analyzed pulmonary mechanics and structure of wildtype and RAGE deficient (RAGE-/-) mice. RAGE deficiency spontaneously resulted in a loss of lung structure shown by an increased mean chord length, increased respiratory system compliance, decreased respiratory syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 61 publications
4
42
0
Order By: Relevance
“…There is also evidence that bleomycin damages epithelial cells in the pulmonary fibrosis process (Jin et al 2018 ), thus genetic variants influencing epithelial cell function could affect susceptibility to fibrosis. For example, Ager encodes a surface protein expressed on the lung epithelium (Wolf et al 2017 ), and candidate gene association studies have reported an increased risk (Yamaguchi et al 2017 ) or no increased risk (Manichaikul et al 2017 ) of the related trait of idiopathic pulmonary fibrosis in patients carrying an AGER minor allele. In addition, Cyp21a1 encodes a hydroxylase expressed in the epithelium of the developing lung (Gilbert et al 2017 ) and deficiencies in this hydroxylase result in congenital adrenal hyperplasia (El-Maouche et al 2017 ), while the product of Tnxb is an extracellular matrix glycoprotein whose variants are associated with the connective tissue fragility of Ehlers–Danlos Syndrome (Chen et al 2016 ; Mao et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that bleomycin damages epithelial cells in the pulmonary fibrosis process (Jin et al 2018 ), thus genetic variants influencing epithelial cell function could affect susceptibility to fibrosis. For example, Ager encodes a surface protein expressed on the lung epithelium (Wolf et al 2017 ), and candidate gene association studies have reported an increased risk (Yamaguchi et al 2017 ) or no increased risk (Manichaikul et al 2017 ) of the related trait of idiopathic pulmonary fibrosis in patients carrying an AGER minor allele. In addition, Cyp21a1 encodes a hydroxylase expressed in the epithelium of the developing lung (Gilbert et al 2017 ) and deficiencies in this hydroxylase result in congenital adrenal hyperplasia (El-Maouche et al 2017 ), while the product of Tnxb is an extracellular matrix glycoprotein whose variants are associated with the connective tissue fragility of Ehlers–Danlos Syndrome (Chen et al 2016 ; Mao et al 2002 ).…”
Section: Discussionmentioning
confidence: 99%
“…53 Alveolar epithelial cells isolated from RAGEdeficient mice are also impaired, exhibiting defective barrier formation. 53 In a model of acute lung injury induced by LPS, leukocyte infiltration into the lung was decreased, suggesting that RAGE regulates lung dynamics through down-regulation of ion channels and/or increased tight junction proteins. 39 This may also explain why RAGE-deficient mice have diminished development of smoke-induced emphysema.…”
Section: Role Of Rage In Chronic and Noninfectious Diseasesmentioning
confidence: 99%
“…In mice lacking RAGE, the structure of the lung is altered, resulting in increased respiratory system compliance, decreased respiratory system elastance, and increased concentrations of serum protein albumin in bronchoalveolar lavage fluid (BALF) 53 . Alveolar epithelial cells isolated from RAGE‐deficient mice are also impaired, exhibiting defective barrier formation 53 .…”
Section: Physiologic Relevance Of Rage In Diseasementioning
confidence: 99%
See 2 more Smart Citations